2018
DOI: 10.1027/1618-3169/a000395
|View full text |Cite
|
Sign up to set email alerts
|

Moral Judgment in Old Age

Abstract: Younger (21-39 years) and older (63-90 years) adults were presented with scenarios illustrating either harmful or helpful actions. Each scenario provided information about the agent's intention, either neutral or valenced (harmful/helpful), and the outcome of his or her action, either neutral or valenced. Participants were asked to rate how morally good or bad the agent's action was. In judging harmful actions, older participants relied less on intentions and more on outcomes compared to younger participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
3
17
0
Order By: Relevance
“…These individuals often show increased condemnation of accidental harms Moran et al, 2011), and recent work has suggested that this may not be due to deficits in the representational ability to attribute intentions but rather limitations in cognitive resources . Our results on state-level reductions in cognitive resources accord well with this prediction, as does other work on trait-level reductions associated with those with autism Moran et al, 2011) or through the course of normal aging (Margoni et al, 2018;.…”
Section: Resource-dependent Conflict Resolutionsupporting
confidence: 88%
See 3 more Smart Citations
“…These individuals often show increased condemnation of accidental harms Moran et al, 2011), and recent work has suggested that this may not be due to deficits in the representational ability to attribute intentions but rather limitations in cognitive resources . Our results on state-level reductions in cognitive resources accord well with this prediction, as does other work on trait-level reductions associated with those with autism Moran et al, 2011) or through the course of normal aging (Margoni et al, 2018;.…”
Section: Resource-dependent Conflict Resolutionsupporting
confidence: 88%
“…Moreover, in one of these studies, the effect of age was larger for judgments of wrongness than for judgment of punishment . Notably, no mediation by working memory or cognitive flexibility (Margoni et al, 2018) was detected, as might have been predicted given our current results. Executive function is a varied construct (Miyake et al, 2000), however, and possibly the inhibition of information about intentions on wrongness judgments posited in our theory attainment hypothesis occurs less through working memory or cognitive flexibility and more through other subtypes of executive function, such as cognitive inhibition.…”
Section: Limitations and Future Directionssupporting
confidence: 76%
See 2 more Smart Citations
“…Higher scores in students for suggested control actions indicate that students are also less tolerant to animal soiling. It has been shown by Margoni et al (2018) that young adults (21-39 years) rely more on intentions and less on outcomes in judging harmful actions, compared to older people (63-90 years), which may motivate them to take stricter measures against a particular AW infringement. A survey of European citizens (European Commission, 2016) showed that young people and students were more interested in the conditions for farm animals.…”
Section: ---mentioning
confidence: 99%